1993
DOI: 10.1111/j.1439-0426.1993.tb00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Haematological studies on four catfish species raised in freshwater ponds in Nigeria

Abstract: A study of the haematological and serological parameters (e throcyte and leucocyte numbers, catfish groups from the fish farm of the African Regional Aquaculture Centre, Aluu, Port Harcourt, Nigeria. Erythrocyte and leucocyte counts showed intra-species variability, while fish size was found to be negatively correlated to haemoglobin concentration and haematocrit values; these are significant at P = 0.05 level. The serological results obtained were found to be similar to the pattern in humans.haematocrit, haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
20
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 11 publications
14
20
3
Order By: Relevance
“…Packed Cell Volume increased with the high concentrations of Derris elliptica (19.0, 22.5g/ml), indicating positive absorption of D. elliptica root powder solution by the fish. PCV could be used to detect haemolysis [21] and is used as a tool for checking anaemic condition in fishes; PCV values are usually between 20% and 35% and scarcely attain values greater than 50% [22]. Mean PCV values in this study fell within this range and were similar to those of H. longifilis [23].…”
Section: Discussionsupporting
confidence: 55%
“…Packed Cell Volume increased with the high concentrations of Derris elliptica (19.0, 22.5g/ml), indicating positive absorption of D. elliptica root powder solution by the fish. PCV could be used to detect haemolysis [21] and is used as a tool for checking anaemic condition in fishes; PCV values are usually between 20% and 35% and scarcely attain values greater than 50% [22]. Mean PCV values in this study fell within this range and were similar to those of H. longifilis [23].…”
Section: Discussionsupporting
confidence: 55%
“…The mean rbc value for H. niloticus is lower than those reported for H. longifilis and H. bidorsalis (ERONDU et al 1993, FAGBENRO et al 1993) but comparable or slightly higher than the values reported for other catfish species C. isheriensis, C. gariepinus and Chrysichthys nigrodigitatus (Lacépède 1803) (KORI-SIAKPERE 1985, ERONDU et al 1993. Except for H. bidorsalis, the mean leucocyte count (wbc) value of H. niloticus is higher than those reported for other catfishes by ERONDU et al (1993).…”
mentioning
confidence: 41%
“…The mean haematocrit value of H. niloticus is comparable to those of African clariid catfishes, C. isheriensis (KORI-SIAKPERE 1985), C. gariepinus Burchell 1822, Heterobranchus longifilis (Valenciennes 1840) (ERONDU et al 1993) and H. bidorsalis (George St. Hilaire 1809) (FAGBENRO et al 1993). The mean rbc value for H. niloticus is lower than those reported for H. longifilis and H. bidorsalis (ERONDU et al 1993, FAGBENRO et al 1993) but comparable or slightly higher than the values reported for other catfish species C. isheriensis, C. gariepinus and Chrysichthys nigrodigitatus (Lacépède 1803) (KORI-SIAKPERE 1985, ERONDU et al 1993. Except for H. bidorsalis, the mean leucocyte count (wbc) value of H. niloticus is higher than those reported for other catfishes by ERONDU et al (1993).…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Packed cell volume did not show any particular pattern resulting from phytase supplement, but values recorded fall within the normal ranges reported for C. gariepinus [25][26][27].…”
Section: Discussionmentioning
confidence: 66%